1996
DOI: 10.1038/hdy.1996.89
|View full text |Cite
|
Sign up to set email alerts
|

Differential seed maturation uncouples fertilization and siring success in Oenothera organensis (Onagraceae)

Abstract: This study examines ovule fertilization and seed maturation success in an evening primrose, Oenothera organensis, using transgenic plants. The reproductive success of several pollen donors was compared using individuals transformed with the GUS (/3-glucuronidase) marker gene which allowed the genotype of developing ovules to be determined prior to seed abortion. This marker gene allowed us to discriminate between a pollen donor's success in fertilizing ovules and its success in siring seeds. Transformed plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…Also, observed differences in gametophyte performance might be masked in the diploid state, thereby obscuring expected fitness differences. This was observed by Havens and Delph (1996) who found that a transformation that affected gametophyte vigor did not affect sporophyte vigor.…”
Section: Discussionmentioning
confidence: 74%
“…Also, observed differences in gametophyte performance might be masked in the diploid state, thereby obscuring expected fitness differences. This was observed by Havens and Delph (1996) who found that a transformation that affected gametophyte vigor did not affect sporophyte vigor.…”
Section: Discussionmentioning
confidence: 74%
“…Because of this, the maternal environment may have a strong influence on embryo development and survival (including seed abortion, e.g. Havens & Delph 1996), and as a result it may be difficult to attribute the events occurring between pollen deposition and fruit maturation unambiguously to paternal or maternal influences, to sporophytic or gametophytic traits.…”
Section: Box 1 Definitions For Analysis Of Seed Paternity In Flowerimentioning
confidence: 99%
“…Color polymorphism of pollen grains ( Jorgensen et al, 2006 ) can be readily assessed, but the discrimination is relatively poor and adaptation is restricted to specifi c species. Although gene transformation ( Havens and Delph, 1996 ;Hudson et al, 2001 ) and differences in ploidy ( Williams et al, 1999 ) can also distinguish pollen genotypes in vivo, these methods are unsuitable for processing the large numbers of samples required for analysis of natural populations.…”
mentioning
confidence: 99%